Staged hybrid open and endovascular exclusion of a symptomatic thoracoabdominal aortic aneurysm in a high-risk patient. (August 2014) - Chung, Christine; Malik, Rajesh; Marin, Michael; Faries, Peter; Ellozy, Sharif
Thoracoabdominal aortic aneurysms have a higher prevalence in the elderly, who are often poor surgical candidates. These extensive aneurysms may be lethal if left untreated. Conventional open repair has proven to be a major task, involving cardiopulmonary bypass, aortic cross-clamping and expeditious repair of an inaccessible structure involving two body cavities. Endovascular repair has become a viable option to treat isolated descending thoracic aneurysms and infrarenal abdominal aortic aneurysms. However, endovascular techniques alone have been less applicable for treating complex aortic aneurysms, including those involving visceral vessels. Therefore, a hybrid open and endovascular approach with visceral debranching has become an increasingly favorable alternative for patients with these complex conditions. We report a case in which a staged hybrid approach was used for successful exclusion of an extensive thoracoabdominal aortic aneurysm in a symptomatic, high-risk patient who would not have been an appropriate candidate for open surgical repair.